PENGARUH DARI PEMBERIAN PROBIOTIK LACTOBACILLUS PLANTARUM DALAM TATA LAKSANA DERMATITIS ATOPIK - Izzah Faidah; Lukman Ariwibowo (Perhimpunan Dokter Spesialis Kulit dan Kelamin Indonesia (PERDOSKI), 2022)
The Effect of Probiotics Lactobacillus plantarum in Management of Atopic Dermatitis ABSTRACT Lactobacillus plantarum is one of probiotics from Indonesian traditional food which is isolated from cow milk. One of the function from probiotics is reduce allergic reaction. Atopic dermatitis is skin inflammation which are chronic and recurrent with accompanied by allergic reaction. This finding to search the effect of probiotics Lactobacillus plantarum in management of Atopic Dermatitis with rated by SCORAD index, the effectivity giving by single or mixture of probiotics, and the side effects of probiotics. This finding using literature review as method. Populations in this finding are 10 articles about probiotics and atopic dermatitis in international journal which had SCIMAGO index at 2017 until 2022. The results of this finding are there is significancy decline of SCORAD index, the mixture of probiotics are better than single probiotic, and there is no side effects reported. The conclusion this finding is there is effect of giving probiotics Lactobacillus plantarum in atopic dermatitis management. Key words: atopic dermatitis, Lactobacillus plantarum, SCORAD